IN LABORATORY GENERATION AND MATURATION OF HUMAN MONOCYTE-DERIVED DENDRITIC CELLS FOR CANCER IMMUNOTHERAPY - MISHRA, KANCHAN K.; BHARADVA, SUMIT; JOSHI, MEGHNAD G.; GULBAKE, ARVIND (International Journal of Applied Pharmaceutics, 2020)
Dendritic cells (DCs) play a critical role in the regulation of adaptive immune responses, furthermore they act as a bridge between the innate and the adaptive immune systems they have been ideal candidates for cell-based immunotherapy of cancers and infections in humans. The first reported trial using DCs in 1995, since they have been used in trials all over the world for several of indications, including cancer and human immunodeficiency virus infection. Generally, for in vitro experiments or for DCs vaccination monocyte-derived dendritic cells (moDCs) were generated from purified monocytes that isolated from peripheral blood by density gradient centrifugation. A variety of methods can be used for enrichment of monocytes for generation of clinical-grade DCs. Herein we summarized up to date understanding of systems and inputs used in procedures to differentiate DCs from blood monocytes in vitro.